Prevalences of inherited red blood cell disorders in pregnant women of different ethnicities living along the Thailand-Myanmar border - Bancone, G; Gilder, ME; Chowwiwat, N; Gornsawun, G; Win, E; Cho, WW; Moo, E; Min, AM; Charunwatthana, P; Carrara, VI; White, NJ; Nosten, F; et al. (F1000Research, 2017)
Background: Inherited red blood cell disorders are prevalent in populations living in malaria endemic areas; G6PD deficiency is associated with oxidant-induced hemolysis and abnormal hemoglobin variants may cause chronic anemia. In pregnant women, microcytic anemia caused by hemoglobinopathies mimics iron deficiency, complicating diagnosis and treatment. Anemia during pregnancy is associated with morbidity and mortality. The aim of this study was to characterize the prevalence of G6PD deficiency, hemoglobinopathies, ABO and Rhesus blood groups among the pregnant population living along the Thailand-Myanmar border. Pregnant women attending antenatal clinics in this area belong to several distinct ethnic groups. Methods: Data was available for 13,520 women attending antenatal care between July 2012 and September 2016. Screening for G6PD deficiency was done by fluorescent spot test routinely. G6PD genotyping and quantitative phenotyping by spectrophotometry were analyzed in a subsample of women. Hemoglobin variants were diagnosed by HPLC or capillary electrophoresis and molecular methods. Blood groups were diagnosed by agglutination test. The prevalence and distribution of inherited red blood cell disorders and blood groups was analyzed with respect to ethnicity. Results: G6PD deficiency was common, especially in the Sgaw Karen ethnic group, in whom the G6PD Mahidol variant allele frequency was 20.7%. Quantitative G6PD phenotyping showed that 60.5% of heterozygote women have an intermediate enzymatic activity between 30% and 70% of the population median. HbE, beta-thalassemia trait and alpha-thalassemia trait were found in 31.2% of women. Only 0.15% of women were Rhesus negative. Conclusions: Distribution of G6PD and hemoglobin variants varied among the different ethnic groups, but the prevalence was generally high throughout the cohort. These findings encourage the implementation of an extended program of information and genetic counseling to women of reproductive age and will help inform future studies and current clinical management of anemia in the pregnant population in this region.